Micro‐fractional, directional skin tightening: A porcine model. Issue 3 (2nd December 2015) - Russe, Elisabeth; Purschke, Martin; Farinelli, William A.; Wang, Ying; Doukas, Apostolos G.; Limpiangkanan, Wikunda; Sakamoto, Fernanda H.; Tam, Joshua; Wechselberger, Gottfried; Anderson, Richard Rox
Abstract : Background and Objective: Skin changes are among the most visible signs of aging. Fractional ablative lasers improve skin quality by making small skin wounds that heal rapidly without scarring. While they improve skin texture and discoloration, there is minimal effect on skin laxity. This study was performed to assess skin shrinkage performed by removing multiple small full‐thickness skin columns with coring needles combined with wound closure. Materials and Methods: In 5 swine 116 squares (3 cm 2 ) were demarcated for treatment and control sites. In treatment sites 10% of the skin was removed by full‐thickness skin coring needles (19 gauge) and afterwards closed and compressed with an elastic adhesive dressing. This procedure was compared to puncturing the skin with standard hypodermic needles (without tissue removal) and subsequent closure with compressive dressing. Area and shape of sites were measured before and 28 days after treatment. Results: Test and control sites healed within a week without scarring. Coring with wound closure caused significant shrinkage after 28 days. The treated skin area was reduced by 9% ( P  < 0.0001) and the direction of shrinkage was influenced by the direction of wound closure. Coring without wound closure and puncturing the skin without tissue removal produced an insignificant 3% decrease in area. Conclusion: Significant minimally invasive skin tightening in a preferred direction can be achieved by removing skin with coring needles followed by wound closure. The direction of shrinkage is influenced by the direction of micro‐hole closure, irrespective of the skin tension lines. This approach may allow reshaping the skin in a desired direction without scarring. Lasers Surg. Med. 48:264–269, 2016. © 2015 Wiley Periodicals, Inc.